2020
DOI: 10.1177/1533033820964131
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Site of Distant Metastasis and Surgical Interventions in Metastatic Gastric Cancer: A Population-Based Study

Abstract: Background: Studies on the prognostic significance of site-specific distant metastasis, multiple-site metastases, and the impact of surgery of the primary tumor and metastatic lesion on survival outcomes of patients with metastatic gastric cancer (GC) remain elusive. Therefore, this study aimed to investigate the prognostic significance of the site of distant metastasis among patients with metastatic GC. Furthermore, the effect of surgery of the primary tumor and metastatic lesion on the prognosis of metastati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…26 , 31 This may be related to the limited effective treatment for MOM. Meantime, the same with previous literature, 27 , 32 our data showed that patients received surgery, chemotherapy or radiation therapy earned higher survival rates, indicated that despite elderly patients have reduced physical function, positive treatment could still provide survival benefits if the body could tolerate it. With further research, the association between gender and lung cancer prognosis is being increasingly reported.…”
Section: Discussionsupporting
confidence: 89%
“…26 , 31 This may be related to the limited effective treatment for MOM. Meantime, the same with previous literature, 27 , 32 our data showed that patients received surgery, chemotherapy or radiation therapy earned higher survival rates, indicated that despite elderly patients have reduced physical function, positive treatment could still provide survival benefits if the body could tolerate it. With further research, the association between gender and lung cancer prognosis is being increasingly reported.…”
Section: Discussionsupporting
confidence: 89%
“…This may be why the liver is the first organ of distant metastasis in patients with GC (6). Due to advancements in medical technologies and the continuous improvement of detection methods, cases of liver metastasis can be detected in early or even asymptomatic stages (23).…”
Section: Discussionmentioning
confidence: 99%
“…In all survival analyses, patients lost to follow‐up were censored at time lost. The factors in the analysis were chosen as covariates because each is either a known prognostic factor for gastrointestinal cancer or has been shown to be related to health or healthcare disparities 23–30 . Age and year of diagnosis were categorized as binary variables.…”
Section: Methodsmentioning
confidence: 99%
“…The factors in the analysis were chosen as covariates because each is either a known prognostic factor for gastrointestinal cancer or has been shown to be related to health or healthcare disparities. [23][24][25][26][27][28][29][30] Age and year of diagnosis were categorized as binary variables. An age cutoff of 65 was chosen as previous studies have demonstrated increased risk for adverse outcome after treatment of gastrointestinal cancers beginning at age ≥65.…”
Section: Primary Statistical Analysismentioning
confidence: 99%